The Effects of COVID-19 on the Emotional and Social Stability, Motivation and Attitudes of Gifted and Non-Gifted Children in Greece - Alexandros Papandreou; Alkistis Mavrogalou; Aristodemos-Theodoros Periferakis; Argyrios Periferakis; Ioana Anca Badarau; Ovidiu Popa-Velea; Cristian Scheau (MDPI AG, 2023)
Gifted children exhibit advanced cognitive abilities, usually beyond their emotional development, which puts them at higher risk of the negative consequences of isolation. This study investigates the effects of distance learning and home confinement on the emotional and social stability, motivation, and attitudes of gifted and non-gifted children in Greece. Our study includes two subsets, from before (September 2017 to March 2020) and after the outbreak of the COVID-19 pandemic (April 2020 to March 2022). The analysis indicated that home confinement and distance learning caused children to create a stronger attachment with their parents, and it increased the involvement of parents in their child's school experience. Non-gifted children displayed high levels of certain attitudes (perfectionism, desire for acceptance, and condescending behavior) and demonstrated elevated motivation. Gifted children in the pre-COVID-19 period had already displayed increased levels of condescending attitude, which is assumed to be the result of already existing expectations from their parents. The pandemic further increased this attitude, as a result of the higher expectations of their parents. Overall, the study highlighted the importance of children to have more than one support system and the need for them to strengthen their self-image.